The Impact of Entrepreneurial Competency on the Empowerment of Community Learning Centre Managers - Erna Ambarini; Karta Sasmita; Adi Irvansyah (Journal of Nonformal Education, 2025)
Background -. Educational disparities, dropout rates, and limited PKBM (Community Learning Center) management capacity remain key challenges. This study takes Bekasi Regency—an urban–semi-urban area with strong entrepreneurial commitment—as its research locus. Research Urgency - Strengthening the managerial and entrepreneurial capacity of PKBM leaders is crucial to sustaining Indonesia’s non-formal education ecosystem. Despite the government’s focus on lifelong learning and community empowerment, many PKBMs struggle to operate independently due to weak institutional management, limited innovation, and low digital adaptation. Addressing this issue is urgent to ensure that community-based education remains relevant, financially viable, and aligned with the goals of inclusive human development in the digital era. Research Objective - This study aims to analyze the effect of entrepreneurial competencies on the empowerment of PKBM managers in Bekasi Regency, and to identify generational patterns in management practices. The research further seeks to propose a competency-based empowerment model that integrates entrepreneurial skills, innovation, and digital networking to enhance the sustainability of community learning centers. Research Methods - This study uses a sequential explanatory mixed-methods design to examine the relationship between entrepreneurial competencies and PKBM managers’ empowerment in Bekasi Regency. Quantitative data from 50 purposively sampled managers were analyzed using CFA and PLS-SEM, while qualitative interviews provided contextual insights, validated through triangulation Research Findings - Entrepreneurial competencies show a strong positive association with PKBM managers’ empowerment (path coefficient = 0.971, p < 0.001), accounting for 94.2% of the variance explained by the model. The analysis also indicates a generational divide: senior managers (>7 years’ experience) tend to rely on trial-and-error approaches (78%), whereas junior managers (<3 years) display higher levels of innovation (92%) but face limitations in professional networking Research Conclusion  - This study demonstrates that entrepreneurial competencies significantly strengthen the empowerment of PKBM (Community Learning Center) managers, while revealing a generational management gap - senior managers rely more on traditional approaches whereas junior managers exhibit greater innovation but face networking constraints. The findings underscore the importance of implementing financial training, cross-generational mentoring, and digital network strengthening programs to transform PKBMs into self-sufficient institutions that support national educational development, with further research needed to adapt this model across different regions by accounting for local contextual factors and technological integration Research Novelty/ Contribution - This study proposes a competency-based empowerment model for PKBM managers that demonstrates empirical validity within the research context, while acknowledging limitations related to sample size, geographic scope, and reliance on self-reported data. Its practical contribution lies in offering a context-specific intervention framework tailored for urban–semi-urban areas in developing countries. By bridging theory with field implementation, the study provides both theoretical insights and applied relevance for strengthening non-formal education in Indonesia, particularly in addressing management challenges faced by community learning centers.